2009
DOI: 10.1016/j.trf.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of following headway in congested traffic

Abstract: This paper reports on results of a study undertaken in the U.K. aimed at investigating factors affecting the car following process. An understanding of the factors affecting this complex decision making process is essential to a wide range of theoretical issues including driver workload, capacity and the modeling of freeway flow, as well as practical applications such as the design of in-vehicle driver aids and assistance systems, many of which have direct relevance to increasing driver safety. The study used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(57 citation statements)
references
References 26 publications
6
50
0
1
Order By: Relevance
“…Both Tsukuba drivers and Southampton drivers spend more time with the short THW (0.5s to 1.5s). As mentioned in previous research (Brackstone et al, 2009), THW tends to decrease as velocity increases. Figure 7 presents the relative velocity-acceleration mapping obtained from the fuzzy inference specification in Tsukuba and Southampton.…”
Section: Static Aspectsupporting
confidence: 74%
“…Both Tsukuba drivers and Southampton drivers spend more time with the short THW (0.5s to 1.5s). As mentioned in previous research (Brackstone et al, 2009), THW tends to decrease as velocity increases. Figure 7 presents the relative velocity-acceleration mapping obtained from the fuzzy inference specification in Tsukuba and Southampton.…”
Section: Static Aspectsupporting
confidence: 74%
“…Research has shown drivers to be relatively accurate when judging distance to a preceding vehicle but poor when judging time (de Vos, Theeuwes, Hoekstra, & Coemet, 1997;Taieb-Maimon & Shinar, 2001). Furthermore, some studies have shown drivers to follow larger vehicles at shorter gaps even though visibility is reduced (Brackstone, Waterson, & McDonald, 2009;Sayer, Mefford, & Huang, 2000).…”
Section: Driving Behaviormentioning
confidence: 99%
“…Whilst a high ICC coefficient was observed for TTC to lead vehicles indicating high test-retest reliability, the high CV value for this variable suggests a large intra-individual variation in car following behavior. Recent work by Brackstone et al (2009) suggests that drivers are inconsistent in their choice of headway, with individual variations above 19% in adopted headway observed between trials in their study. Collectively, these results suggest that driving headway is likely to be susceptible to intra-individual differences.…”
Section: Discussionmentioning
confidence: 96%